Effects of human donor milk on gut barrier function and inflammation: in vitro study of the beneficial properties to the newborn - Rodríguez-Camejo, Claudio; Puyol, Arturo; Arbildi, Paula; Sóñora, Cecilia; Fazio, Laura; Siré, Gabriela; Hernández, Ana (Frontiers in Immunology, 2023)
The gastrointestinal and immune systems of premature infants are not fully developed, rendering them more vulnerable to severe complications like necrotizing enterocolitis. Human milk offers a rich array of bioactive factors that collectively contribute to reducing the incidence of gut infections and inflammatory conditions. When a mother's milk is unavailable, preterm infants are often provided with donor human milk processed in Human Milk Banks. However, it remains uncertain whether pasteurized milk confers the same level of risk reduction as unprocessed milk.This uncertainty may stem from the well-documented adverse effects of heat treatment on milk composition. Yet, our understanding of the comprehensive impact on protective mechanisms is limited. In this study, we conducted a comparative analysis of the effects of raw versus pasteurized milk and colostrum versus mature milk on cellular functions associated with the gut epithelial barrier and responses to inflammatory stimuli. We utilized THP-1 and HT-29 cell lines, representing monocyte/macrophages and gut epithelial cells, respectively. Our observations revealed that all milk types stimulated epithelial cell proliferation. However, only raw colostrum increased cell migration and interfered with the interaction between E. coli and epithelial cells. Furthermore, the response of epithelial and macrophage cells to lipopolysaccharide (LPS) was enhanced solely by raw colostrum, with a milder effect observed with mature milk. In contrast, both raw and pasteurized milk diminished the LPS induced response in monocytes. Lastly, we examined how milk affected the differentiation of monocytes into macrophages, finding that milk reduced the subsequent inflammatory response of macrophages to LPS. Our study sheds light on the impact of human milk on certain mechanisms that potentially account for its protective effects against necrotizing enterocolitis, highlighting the detrimental influence of pasteurization on some of these mechanisms. Our findings emphasize the urgency of developing alternative pasteurization methods to better preserve milk properties. Moreover, identifying the key components critically affected by these protective mechanisms could enable their inclusion in donor milk or formula, thereby enhancing immunological benefits for vulnerable newborns.